2019
DOI: 10.1016/j.joca.2019.02.260
|View full text |Cite
|
Sign up to set email alerts
|

A2A adenosine receptor stimulation regenerates cartilage in osteoarthritis animal model

Abstract: Methods: Ext1 was stably knocked down or overexpressed in ATDC5 chondrogenic cells cultured as micromasses. HS content was determined using ELISA. Gene expression of chondrogenic markers (Col2a1, Acan andSox9) and direct Wnt target genes (Axin2 andLef1) was measured by RT q-PCR, at day 1, 7 and 14 of the chondrogenic differentiation process. Total proteoglycan content was evaluated by Alcian blue staining and DMMB assay. Activation of canonical Wnt signaling was

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…OA is a common and chronic rheumatologic, metabolic, and degenerative disease for which medical therapies are limited, expensive, and ineffective . Liposomal preparations of adenosine or the A2AR‐specific, CGS21680 have been shown to modulate OA progression by restoring cartilage volumes in established OA models of PTOA and obesity‐induced OA . The results here presented suggest that A2AR agonism also improves mitochondrial dynamics and function in inflamed human chondrocytic cells which promotes chondrocyte homeostasis, healing, and subsequent preservation of cartilage.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…OA is a common and chronic rheumatologic, metabolic, and degenerative disease for which medical therapies are limited, expensive, and ineffective . Liposomal preparations of adenosine or the A2AR‐specific, CGS21680 have been shown to modulate OA progression by restoring cartilage volumes in established OA models of PTOA and obesity‐induced OA . The results here presented suggest that A2AR agonism also improves mitochondrial dynamics and function in inflamed human chondrocytic cells which promotes chondrocyte homeostasis, healing, and subsequent preservation of cartilage.…”
Section: Discussionmentioning
confidence: 99%
“…Mouse and rat knees were decalcified after sacrifice, removal of soft tissue, and fixation (4% ofPFA for 48 hours) in 10% of EDTA (7.4 pH) for 4 weeks. Parafilm-embedded histological sections (5 µm) were cut, mounted, and prepared for immunohistochemistry for mitochondrial markers (anti-ATPase (1/1000 dilution), anti-8-OHg (1/200 dilution)) as previously described [14]. Briefly, slides are incubated at 60°C for 30 minutes and deparaffinized by soaking in pure xylene for 10min three times.…”
Section: Histology Immunohistochemistry and Immunofluorescencementioning
confidence: 99%
See 1 more Smart Citation
“…As predicted by our KEGG pathway analysis and previously published work on the A2ARKO mouse, most of the differences in gene expression could be explained by activation of transcription factors such as NF-κB and its downstream signaling elements. Among affected genes associated with pro-inflammatory and catabolic processes, SMAD3 is of particular interest since our group has demonstrated that in vitro and in vivo ligation of A2AR promotes nuclear localization of phosphorylated SMAD2/3 which is associated with maintenance of cartilage [6,7]. Increased SMAD3 expression in the null chondrocytes may, therefore, represent compensatory expression.…”
Section: Discussionmentioning
confidence: 99%
“…Application of liposomal preparations of either adenosine or the selective A2AR agonist (CGS21680) abrogates development of OA in models of post-traumatic OA (PTOA) in rats [5,6] and obesity-induced OA in mice [6,7]. Moreover, A2AR null mice develop spontaneous OA by 16 weeks [5,8].…”
Section: Introductionmentioning
confidence: 99%